Book Reviews - Irene Papoulis; Wendy Ryden; Mark McBeth; Mary Pigliacelli (Journal of the Assembly for Expanded Perspectives on Learning, 2018)
Irene Papoulis: Looking for Solace Wendy Ryden: Golub, Adam and Heather Richardson Hayton, eds. Monsters in the Classroom: Essays on Teaching What Scares Us. Jefferson, NC: McFarland and Company, Inc., 2017. Mark McBeth: Waite, Stacey. Teaching Queer: Radical Possibilities for Writing and Knowledge. Pittsburgh: U of Pittsburgh Press, 2017. Mary Pigliacelli: Eodice, Michele, Anne Ellen Geller, and Neal Lerner. The Meaningful Writing Project: Learning, Teaching, and Writing in Higher Education. Boulder, Utah State UP, 2016.